P‐137: Polymer‐Stabilized Blue‐Phase Liquid‐Crystal Fresnel Lens Cured by Patterned Light Using a Spatial Light Modulator. Issue 1 (May 2016) - Rong, Na; Li, Yan; Yuan, Yachao; Li, Xiao; Zhou, Pengcheng; Huang, Shuaijia; Liu, Shuxin; Lu, Jiangang; Su, Yikai
Abstract : A novel fabrication method for polymer‐stabilized blue‐phase liquid‐crystal Fresnel lens is proposed. Blue phase is stabilized by patterned light illumination directly obtained from a spatial light modulator. The lens diffraction efficiency can be continuously tuned. With full programmable capability, this method holds great potential in optical applications.